15.3k views
0 votes
Lost as usual yep I am

Lost as usual yep I am-example-1
User NabilS
by
5.2k points

2 Answers

6 votes

Answer:

y=-3x-4

Explanation:

If you are looking for a line that is perpendicular to the given line, you will need to:

1) Find slope of given line. You could do this by solving for y to put it into slope-intercept form, y=mx+b. m is the slope while b is the y-intercept.

2) Once you found slope of given line you can use it find the slope of line perpendicular to the given line. Perpendicular lines have opposite reciprocal slopes.

3) Then you can use point-slope form since you know a point (x1,y1) and you would have found the slope in 2).

Point-slope form is:

y-y1=m(x-x1)

where m is the slope and (x1,y1) is a point that you know is on the line.

4) The goal is y=mx+b form so you will need to get y by itself and distribute & simplify.

1)

7x-21y=39

Subtract 7x on both sides:

-21y=-7x+39

Divide both sides by -21:

y=(-7x)/(-21)+(39)/(-21)

Simplify fractions:

y=(x/3)-(13/7)

or

y=(1/3)x-(13/7)

The slope is 1/3.

2) The opposite reciprocal of 1/3 is -3/1=-3.

3)

y-5=-3(x--3)

y-5=-3(x+3)

4)

Add 5 on both sides:

y=-3(x+3)+5

Distribute-3 to terms inside the ( ):

y=-3x-9+5

Combine like terms:

y=-3x-4

User Danem
by
5.8k points
3 votes

Answer:

y = -3x -4

Explanation:

A perpendicular line has a slope that is the negative reciprocal of that of the given line. When the equation starts out in standard form, a line with negative reciprocal slope can be written by swapping the x- and y-coefficients and negating one of them.

The given x- and y-coefficients have the ratio 1:-3, so we can use the coefficients 3 and 1 for our purpose.

The usual process of making the line go through a given point can be used. That is, we can translate the line from the origin to the desired point by subtracting the point coordinates from x and y. Then we have ...

3(x+3) +(y-5) = 0

__

This is "an" equation. It is in no particularly recognizable form. It can be rearranged to the form y = mx + b:

3x +9 +y -5 = 0 . . . . . eliminate parentheses

y = -3x -4 . . . . . subtract terms that are not "y"

Lost as usual yep I am-example-1
User Lundahl
by
5.0k points